Case report: Myelitis and ganglionitis, an atypical presentation of Hansen’s disease - Spitz, Clarissa Neves; Pitta, Izabela Jardim R.; Andrade, Ligia; de Carvalho, Larissa Bittencourt; de Carvalho, Diogo Matheus Terrana; Schmidt, Felipe da Rocha; Siquara de Sousa, Ana Caroline; Mendonça, Silvana Machado; Sarno, Euzenir Nunes; Sales, Anna Maria; Pinheiro, Roberta Olmo; Jardim, Marcia Rodrigues (Frontiers in Medicine, 2024)
Hansen’s disease, or leprosy, is a disease characterized by dermatological and neurological disorders. A neural form also exists, in which peripheral neuropathy occurs in the absence of skin lesions. However, cases of leprosy that involve the central nervous system and proximal nerves are rare in the literature. We describe the case of an oligosymptomatic patient diagnosed with the neural form of leprosy with involvement of peripheral nerves, dorsal root ganglion, and cervical spinal cord in an atypical presentation of the disease. Through complementary examinations and nerve biopsies, the bacillus was identified, and treatment was subsequently initiated. This case highlights the importance of investigating the suspicion of leprosy, even in cases with atypical manifestations, as early diagnosis and treatment can reduce neurological damage and deformities.